Use of paclobutrazol and ethylene in the potted production of ornamental pineapple - Tellez, Hayver Olaya [UNESP]; do Bomfim, Guilherme Vieira; de Carvalho, Ana Cristina Portugal Pinto; de Azevedo, Benito Moreira (FapUNIFESP (SciELO), 2023)
The expansion of residential areas has increased the demand for exotic and increasingly compact landscape plants. In this context, this work aimed to evaluate the effects of paclobutrazol (PBZ) and the timing of ethylene application on growth reduction and flowering anticipation in ornamental pineapples grown in pots. The randomized block design was used with factorial arrangement (2 x 5) and 4 replications and 4 plants per plot. The primary treatments are the presence and absence of PBZ. The secondary treatments were five times of floral induction with ethylene: 90; 120; 150; 180; 210 days after transplanting (DAT) the seedlings into the pots. It was evaluated the variables: height ratio between the heights of the pot and the plant; rosette diameter; leaves length ‘D’ and flowering index. At 255 DAT, although the plants did not respond to floral induction with ethylene, only those treated with PBZ were more compact and had different characteristics such as smaller size and a ratio below 1/3 of the height of the vase in relation to the plant that to favor its commercialization, in pot.
Uso de paclobutrazol e etileno na produção envasada de abacaxizeiro ornamental
Keywords: Ananas comosus L.; floral induction; plant growth regulator